Glucagonocentric restructuring of diabetes: a pathophysiologic and therapeutic makeover - Roger H. Unger; Alan D. Cherrington (The Journal of Clinical Investigation, 2012)
The hormone glucagon has long been dismissed as a minor contributor to metabolic disease. Here we propose that glucagon excess, rather than insulin deficiency, is the sine qua non of diabetes. We base this on the following evidence: (a) glucagon increases hepatic glucose and ketone production, catabolic features present in insulin deficiency; (b) hyperglucagonemia is present in every form of poorly controlled diabetes; (c) the glucagon suppressors leptin and somatostatin suppress all catabolic manifestations of diabetes during total insulin deficiency; (d) total β cell destruction in glucagon receptor–null mice does not cause diabetes; and (e) perfusion of normal pancreas with anti-insulin serum causes marked hyperglucagonemia. From this and other evidence, we conclude that glucose-responsive β cells normally regulate juxtaposed α cells and that without intraislet insulin, unregulated α cells hypersecrete glucagon, which directly causes the symptoms of diabetes. This indicates that glucagon suppression or inactivation may provide therapeutic advantages over insulin monotherapy.